A case report of a tongue ulcer presented as the first sign of occult tuberculosis - Seo-Yeong Kim; Jin-Seok Byun; Jae-Kap Choi; Jae-Kwang Jung (BMC, 2019)
Abstract Background Tuberculosis (TB) is a serious infectious disease with considerable fatality, typically affecting the pulmonary system and, rarely, other body organs including the oral cavity. Due to the rarity of oral TB, it is frequently overlooked in differential diagnosis of oral lesions. Despite a declining trend in TB incidence in recent years, it is still a major public health problem with high contagiousness, thereby requiring the early diagnosis and prompt treatment. Case presentation A 57-year-old male patient presented with chief complaint of painful ulcer on tip of his tongue. He reported that the ulcer developed without any remarkable event such as mechanical trauma, vesicle formation or systemic illness. His past medical history revealed the TB over 40 years ago, which had reportedly healed after pharmacological treatments. As the ulceration persisted after topical steroid application and careful education about avoiding possible mechanical stimuli, biopsy was performed and histological finding showed typical findings of oral tuberculosis including intense granulomatous inflammatory features with small red rods of mycobacterial organisms as well as epithelioid cells and Langhans giant cells. After suitable antituberculosis treatments, oral tuberculosis ulcer was almost completely healed. We present a case of oral TB affecting tip of the tongue in a patient with a history of pulmonary TB and emphasize the understanding of intraoral manifestations for early diagnosis and prompt treatment of TB. Conclusions The present case represented the importance of understanding oral tuberculosis manifestations for dental clinicians who might be frequently the first health care professionals to encounter various oral lesions.